Space Environments and Effects on CIGS Solar Cells and Modules. Issue 1792 (14th May 2015) - Kawakita, Shirou; Imaizumi, Mitsuru; Kusawake, Hiroaki
ABSTRACT: Cu (In, Ga) Se2 (CIGS) thin-film solar cells are optimal solar cells for spacecraft, since they have high efficiency, lightweight, flexible and high radiation tolerance. The CIGS solar module without a coverglass to prevent degradation in space has been demonstrated with a small satellite and its electrical performance indicates no degradation as predicted from ground tests. However, the cells need to prevent the damages from other effects in space. The paper introduces some space environment tests and how to improve performance in CIGS cells for spacecraft.